Steganography: Text File Hiding in Image - Yaw Choon, Kit (2013)
Steganography is the art or science in hiding. It is origin from the Greek work where stegano(hiding) + graphy(writing). It is hiding a message rather than encoding it. Basically it can be understand as hiding something into another something else. The something else which embedded the hidden object look no differ from original, thus it is hard to arise suspicious from others. Through the concept of steganography, this research wishing to hide the text file in the image. The purpose to doing so is to create a steganographic message when only sender and receiver know the trick behind the steganographic message.